2012
DOI: 10.1371/journal.pone.0051469
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Apoptosis Are Differentially Induced in Neurons and Astrocytes Treated with an In Vitro Mimic of the Ischemic Penumbra

Abstract: The development of clinical stroke therapies remains elusive. The neuroprotective efficacies of thousands of molecules and compounds have not yet been determined; however, screening large volumes of potential targets in vivo is severely rate limiting. High throughput screens (HTS) may be used to discover promising candidates, but this approach has been hindered by the lack of a simple in vitro model of the ischemic penumbra, a clinically relevant region of stroke-afflicted brain. Recently, our laboratory devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…Species-specific responses may be an additional complicating factor in the study of neural death, as well as inter-area anatomical/functional differences. For example, contrasting results were obtained after ischemia or stroke in several mammalian species, as mixed apoptotic/necrotic figures were described in rat (Wei et al, 2006) or mouse (Pamenter et al, 2012), whereas no evidence of apoptosis was described in gerbils (Colbourne et al, 1999), and apoptosis and necrosis occurred in separate neuronal populations in dogs (Martin et al, 2000). Likewise, death in prionic infection was reported to be autophagic by some authors (Liberski et al, 2008) but others denied the occurrence of autophagy and, instead, described a novel, non-apoptotic, non-autophagic form of neuronal death in a transgenic mouse model (Christensen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific responses may be an additional complicating factor in the study of neural death, as well as inter-area anatomical/functional differences. For example, contrasting results were obtained after ischemia or stroke in several mammalian species, as mixed apoptotic/necrotic figures were described in rat (Wei et al, 2006) or mouse (Pamenter et al, 2012), whereas no evidence of apoptosis was described in gerbils (Colbourne et al, 1999), and apoptosis and necrosis occurred in separate neuronal populations in dogs (Martin et al, 2000). Likewise, death in prionic infection was reported to be autophagic by some authors (Liberski et al, 2008) but others denied the occurrence of autophagy and, instead, described a novel, non-apoptotic, non-autophagic form of neuronal death in a transgenic mouse model (Christensen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box O3a and SOD2 are two main substrates of SIRT3. 21 We examined the total protein levels of SIRT3 and FoxO3a from homogenates in the penumbra. Ketones increased SIRT3 (79.0 ± 7.2% ketones versus 53.7 ± 5.5% NS) and FoxO3a levels (66.0 ± 7.8% ketones versus 36.7 ± 2.6% NS) ( Figures 5A and 5C).…”
Section: Ketones Improved Neurologic Function By Reducing Infarct Volumementioning
confidence: 99%
“…Enhancement of autophagic processes was observed in brain after hypoxic-ischemia, 7 and the occurrence of autophagy measured by conversion of LC3-I to LC3-II during brain ischemia has been confirmed by in vivo imaging. 8 Although controversy exists whether autophagy contributes to cell death or cell survival, 9-11 recent observations using inhibitors or modulators of autophagy revealed that autophagy mediates neuronal cell death during ischemia. 12,13 Wen et al 14 observed autophagy in focal cerebral ischemia, and demonstrated that treatment with inhibitors of autophagy significantly reduced brain damage.…”
Section: Introductionmentioning
confidence: 99%